2015
DOI: 10.1080/1755876x.2015.1022350
|View full text |Cite
|
Sign up to set email alerts
|

Building the capacity for forecasting marine biogeochemistry and ecosystems: recent advances and future developments

Abstract: International audienceBuilding the capacity for monitoring and forecasting marine biogeochemistry and ecosystem dynamics is a scientific challenge of strategic importance in the context of rapid environmental change and growing public awareness of its potential impacts on marine ecosystems and resources. National Operational Oceanography centres have started to take up this challenge by integrating biogeochemistry in operational systems. Ongoing activities are illustrated in this paper by presenting examples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 106 publications
1
60
0
Order By: Relevance
“…Ocean colour data assimilation is being increasingly utilized by the reanalysis and forecasting community (Gehlen et al, 2015), and has already been successfully demonstrated for ERSEM (Ciavatta et al, 2011(Ciavatta et al, , 2014. A suitable ocean colour assimilation scheme for operational purposes is being developed as a collaboration between the Met Office and PML, to be implemented in the SSB ERSEM version and run operationally as part of CMEMS.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Ocean colour data assimilation is being increasingly utilized by the reanalysis and forecasting community (Gehlen et al, 2015), and has already been successfully demonstrated for ERSEM (Ciavatta et al, 2011(Ciavatta et al, , 2014. A suitable ocean colour assimilation scheme for operational purposes is being developed as a collaboration between the Met Office and PML, to be implemented in the SSB ERSEM version and run operationally as part of CMEMS.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Analysis to date has suggested that skillful seasonal and, in some cases, multi-annual sea surface temperature predictions are possible for many regions despite coarse model resolution Tommasi et al, 2017b). Seasonal to multi-annual predictions of ocean productivity, oxygen and other potential factors important to marine resource distributions and abundance have provided some cause for optimism (Séférian et al, 2014;Gehlen et al, 2015), but have not been assessed with the same rigor as ocean temperatures, in part due to the sparsity of data with which to robustly characterize the model skill. The use of short-term forecasts in dynamic management approaches (Maxwell et al, 2015;Dunn et al, 2016;Tommasi et al, 2017b) may also contribute to building long-term resilience (Hobday et al, 2016;Tommasi et al, 2017a).…”
Section: Current Approaches For Predicting and Projecting Marine Mammmentioning
confidence: 99%
“…The annual increase also occurs against a background of large spatial variation of, for example, 140 µatm in different regions of the Southern Ocean in spring (Bakker et al, 2008; E. M. . Similarly, seasonal variation of 0.04 in surface pH in the subtropical North Atlantic Ocean (González-Dávila et al, 2007) is 20 times the mean annual decrease in surface ocean pH at a rate of −0.002 yr −1 Lauvset et al, 2015).…”
Section: Introductionmentioning
confidence: 99%